KARAKTERISASI SELULOSA KULIT ROTAN SEBAGAI MATERIAL PENGGANTI FIBER GLASS PADA KOMPOSIT - Siti Nikmatin; Y. Aris Purwanto; Tieneke Mandang; Akhirudin Maddu; Setyo Purwanto (JURNAL AGROTEKNOLOGI, 2011)
Abundant of natural resources in Indonesia give advent to the development of Biocomposite technology. Furthermore, agricultural wastes as one typical sources of bio-composite are available everywhere in Indonesia. Rotan-bark is one kind of agriculture waste that can be use as main input for bio-composite. This research deals with characterisation of cellulose content from rotan-bark as substitute for fibber glass as filler in composite. Cellulose from Rotan-bark made in long and short fibbers by means of fermentation. In this case, aspergillus niger is used as fermentation agent. Rotan type, Rotan mass, and temperature are maintained constant during the treatment. Variable of fermentation time ( tF ) and fungi-volume ( Vf) are varied. Fermentationtime range from: 4,5,6,8 to 10 days. Extraction of rotan-bark-cellulose by means of fermentation developed specific enzyme. This enzyme can break-down the filament of non-cellulose plant. Then this enzyme can separated fibber component from: parenchyma, xylem and epidermis at weight density = 0,58 and optimal efficiency up to 60,8% at tF = 8 days ; Vf = 15 ml. X-Furthermore, XRay Diffraction (XRD) shows the crystallized structure obtained from rotan-bark cellulose at Apparent Crystal Size (ACS) = 29130,42 nm and η (inhomogeneous mechanical micro strain) = 0,94 x 10-3 . Characterization by means of SEM-EDS shows rotan-bark cellulose composed from : C = 47,5 % massa, O = 46 % massa and mineral. The result is close to recommended fibber glass composition for industrial application. Keywords : fibber glass, extraction, celulosa, bio-composite, aspergilus niger